CHARACTER BUILDING OF HONESTY IN THE ACADEMIC DOCUMENTS OF VOCATIONAL SCHOOL IN ENGLISH LANGUAGE SUBJECT - Wahyu Pambayuningsih; Sri Sumarni; Darmahusni (Getsempena English Education Journal, 2021)
This research examined the honesty as part of character building in academic documents of English subject in Vocational high school. Using content analysis, the researcher analyzed the honesty throughout the documents. The data was words, phrases, clauses, sentences, and the pharaprashing of them. The data was taken from Vocational High School’s documents used by English teachers of vocational school. The finding showed that honesty appears explicitly and implicitly. All the aspects of character building of honesty were stipulated in syllabus provided by the government. The indicators of honesty that appear in the lesson plan, learning material, and assessment of English language subject in vocational high school are integrity, academic honesty, and sportsmanship. Those indicators are addressed implicitly in the documents represented by sub indicators such as the prohibition to cheat in doing the assignment and so forth. However, there was no consistency across the documents because honesty indicators appeared quite low in assessment tools prepared by English teachers. This condition indicated that students of Vocational High School get the character building of honesty through English language subject because it was stipulated, and addressed in academic documents. This study proposed a possibility for teachers to improvise their assessment tools by inserting honesty indicators.